NgAgo possesses guided DNA nicking activity. Issue 17 (3rd September 2021) - Lee, Kok Zhi; Mechikoff, Michael A; Kikla, Archana; Liu, Arren; Pandolfi, Paula; Fitzgerald, Kevin; Gimble, Frederick S; Solomon, Kevin V
Abstract: Prokaryotic Argonautes (pAgos) have been proposed as more flexible tools for gene-editing as they do not require sequence motifs adjacent to their targets for function, unlike popular CRISPR/Cas systems. One promising pAgo candidate, from the halophilic archaeon Natronobacterium gregoryi (NgAgo), has been the subject of debate regarding its potential in eukaryotic systems. Here, we revisit this enzyme and characterize its function in prokaryotes. NgAgo expresses poorly in non-halophilic hosts with most of the protein being insoluble and inactive even after refolding. However, we report that the soluble fraction does indeed act as a nicking DNA endonuclease. NgAgo shares canonical domains with other catalytically active pAgos but also contains a previously unrecognized single-stranded DNA binding domain (repA). Both repA and the canonical PIWI domains participate in DNA cleavage activities of NgAgo. NgAgo can be programmed with guides to nick targeted DNA in Escherichia coli and in vitro 1 nt outside the 3′ end of the guide sequence. We also found that these endonuclease activities are essential for enhanced NgAgo-guided homologous recombination, or gene-editing, in E. coli . Collectively, our results demonstrate the potential of NgAgo for gene-editing and provide new insight into seemingly contradictory reports.